Evaluation of Using Titanium Mesh in the Reconstruction of Traumatic Orbital Floor Fracture (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Among the nonresorbable implants, Titanium mesh is the most common graft used for orbital reconstruction. It is continuously improved to achieve accurate restoration of orbital volume. To evaluate the using of Titanium mesh for the reconstruction of traumatic orbital floor fractures. Patients and Methods: A total of (32) patients were enrolled in this study where operated under general anesthesia to repair the orbital floor fractures by using titanium mesh, and they were ( 24 ) males and (8) females. (16) patients had Enophthalmos,( 10) patients had Diplopia,(6) patients had both enophalmos with diplopia; all patients had ecchymosis, Subconjunctival hemorrhage, Parasthesia of infraorbital nerve. Results: The results were well represented as the following: (29)patients(90.62%) had no both diplopia & enophthalmos. Postoperative complication had been found in only( 3) patients (9.3%), Two patients(6.25%) had diplopia, one patient (3.1%) had Enophthalmos. Conclusions: Titanium mesh has a long track record of reconstruction of large orbital floor defects and correction of globe malposition.
Keywords: Titanium mesh; orbital reconstruction and fracture